Development of Functionalized Carbon Nano-Onions Reinforced Zein Protein Hydrogel Interfaces for Controlled Drug Release - Narsimha Mamidi; Aldo González-Ortiz; Irasema Lopez Romo; Enrique V. Barrera (MDPI AG, 2019)
In the current study, poly 4-mercaptophenyl methacrylate-carbon nano-onions (PMPMA-CNOs = f-CNOs) reinforced natural protein (zein) composites (zein/f-CNOs) are fabricated using the acoustic cavitation technique. The influence of f-CNOs inclusion on the microstructural properties, morphology, mechanical, cytocompatibility, in-vitro degradation, and swelling behavior of the hydrogels are studied. The tensile results showed that zein/f-CNOs hydrogels fabricated by the acoustic cavitation system exhibited good tensile strength (90.18 MPa), compared with the hydrogels fabricated by the traditional method and only microwave radiation method. It reveals the magnitude of physisorption and degree of colloidal stability of f-CNOs within the zein matrix under acoustic cavitation conditions. The swelling behaviors of hydrogels were also tested and improved results were noticed. The cytotoxicity of hydrogels was tested with osteoblast cells. The results showed good cell viability and cell growth. To explore the efficacy of hydrogels as drug transporters, 5-fluorouracil (5-FU) release was measured under gastric and intestinal pH environment. The results showed pH-responsive sustained drug release over 15 days of study, and pH 7.4 showed a more rapid drug release than pH 2.0 and 4.5. Nonetheless, all the results suggest that zein/f-CNOs hydrogel could be a potential pH-responsive drug transporter for a colon-selective delivery system.